PERSONAL SELLING ANALYSIS IN PT HONDA KUMALA GROUP - Sorongan, Junita; Pandowo, Merinda H.C (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: In this modern century, the development of Science and Technology is progressing. This encourages the development of an increasingly rapid business world and increasingly fierce market competition, thus demanding the existence of an increasingly good marketing system in every company engaged in industry and services. Based on the formulation of the problem above, the research objectives to be achieved are as follows: To find out consumer behavior in purchasing vehicles at PT. Honda Kumala Group, seen from the price, taste, quality, resale price, and promotion, to find out the most dominant factors affecting consumer behavior in purchasing vehicles at PT. Honda Kumala Group, how is the personal selling of sales staff in PT. Honda Kumala Group?, what is the pss of sales staff in PT.Honda Kumala Group. This research uses a qualitative method that is collecting data by interview. The results of this research from 10 informants from sales in PT. Honda Kumala Group. The findings of this study revealed that three factors have a significant impact on sales involvement on personal selling: Motivation, Approaches, Good Grooming.Â Keywords: personal selling